Carbon Nanotubes Based Black Absorbing Coatings for Pyroelectric and Other Thermal Detector Application - Bravina, S.L.; Morozovsky, N.V.; Dovbeshko, G.I.; Fesenko, O.M.; Obraztsova, E.D. (Наносистеми, наноматеріали, нанотехнології, 2009)
The study of optical and thermophysical characteristics of the absorbing coatings (AC) for sensitive elements of pyroelectric detectors of radiation based on carbon nanotubes paste (CNTP-black) is performed in comparison with those AC formed from gold disperse layer (Au-black) and dielectric lacquer paint (DLP-black). The spectral dependences of reflectance and absorbance of CNTP-black, Au-black and DLP-black in IR-spectrum range 2.5—25 μm are presented. By photothermomodulation method, the frequency spectra of pyroelectric response amplitude and phase are obtained. The estimation of thermal diffusivity values of the investigated blacks as AC for sensitive elements of pyroelectric detectors is performed in situ. Prospects of using CNTP-black based AC for pyroelectric and other thermal detector applications are shown.